Low-Frequency Repetitive Transcranial Magnetic Stimulation for Stroke-Induced Upper Limb Motor Deficit: A Meta-Analysis. (21st December 2017) - Zhang, Lan; Xing, Guoqiang; Shuai, Shiquan; Guo, Zhiwei; Chen, Huaping; McClure, Morgan A.; Chen, Xiaojuan; Mu, Qiwen
Abstract : Background and Purpose . This meta-analysis aimed to evaluate the therapeutic potential of low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) over the contralesional hemisphere on upper limb motor recovery and cortex plasticity after stroke. Methods . Databases of PubMed, Medline, ScienceDirect, Cochrane, and Embase were searched for randomized controlled trials published before Jun 31, 2017. The effect size was evaluated by using the standardized mean difference (SMD) and a 95% confidence interval (CI). Resting motor threshold (rMT) and motor-evoked potential (MEP) were also examined. Results . Twenty-two studies of 1 Hz LF-rTMS over the contralesional hemisphere were included. Significant efficacy was found on finger flexibility (SMD = 0.75), hand strength (SMD = 0.49), and activity dexterity (SMD = 0.32), but not on body function (SMD = 0.29). The positive changes of rMT (SMD = 0.38 for the affected hemisphere and SMD = −0.83 for the unaffected hemisphere) and MEP (SMD = −1.00 for the affected hemisphere and SMD = 0.57 for the unaffected hemisphere) were also significant. Conclusions . LF-rTMS as an add-on therapy significantly improved upper limb functional recovery especially the hand after stroke, probably through rebalanced cortical excitability of both hemispheres. Future studies should determine if LF-rTMS alone or in conjunction with practice/training would be more effective. Clinical Trial Registration Information . This trial is registered with unique identifier CRD42016042181 .